2021
DOI: 10.21037/atm-21-6434
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the rapid recovery of patients who underwent video-assisted thoracoscopic lung surgery under non-intubated anesthesia

Abstract: Background: Non-intubated anesthesia thoracoscopic surgery is an evolving form of minimally invasive thoracic surgery. It has had encouraging results in the treatment of lung cancer, and the current concept of enhanced recovery after surgery has become indispensable to surgical treatment. Our center retrospectively evaluated the clinical effect of rapid postoperative rehabilitation in patients who underwent thoracoscopic lung surgery under non-intubated anesthesia. Methods:The clinical data of 192 patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Most traditional surgical methods involve anterolateral incisions, which are long incisions that lead to a higher blood loss volume, take a longer time to open and to close the chest, and occasionally require the surgeon to cut through the ribs ( 10 ). Therefore, the application of thoracoscopic surgery has greatly reduced postoperative complications and accelerated recovery for patients who experience obvious postoperative pain, have large incision scars, exhibit slow postoperative healing, and have a high incidence of complications ( 11 ). In recent years, with the advancement of endoscopic technology and instruments, minimally invasive surgery has evolved from traditional three-port and two-port to uniportal VATS ( 12 – 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most traditional surgical methods involve anterolateral incisions, which are long incisions that lead to a higher blood loss volume, take a longer time to open and to close the chest, and occasionally require the surgeon to cut through the ribs ( 10 ). Therefore, the application of thoracoscopic surgery has greatly reduced postoperative complications and accelerated recovery for patients who experience obvious postoperative pain, have large incision scars, exhibit slow postoperative healing, and have a high incidence of complications ( 11 ). In recent years, with the advancement of endoscopic technology and instruments, minimally invasive surgery has evolved from traditional three-port and two-port to uniportal VATS ( 12 – 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that nonintubation anesthesia promotes early feeding and ambulation. Simultaneously, because it avoids the use of muscle relaxants, it can reduce the incidence of postoperative vomiting, and the ventilation method of a laryngeal mask or face mask can reduce the possibility of throat injury, reduce the incidence of postoperative throat discomfort, and improve patient satisfaction ( 28 , 29 ). In our study, no significant differences were observed between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, optimizations of anesthetic agent selection and airway management are crucial to guarantee the life safety of asthmatic patients. Non-intubated video-assisted thoracoscopic surgery (NIVATS) has been widely used worldwide because of its advantages of enhanced recovery after surgery (ERAS) ( 4 ). To minimize the perioperative risk of anesthetic management, NIVATS under spontaneous respiration might be an optimal therapeutic option for asthmatic patient who underwent thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%